Evaluating serving capacity of yearling beef bulls - A field trial - G. Boyd; L. Corah (Kansas Agricultural Experiment Station Research Reports, 1987)
Results from two trials showed that serving capacity (SC) can be successfully evaluated in yearling beef bulls under field conditions and is influenced by sire line (P<.01). Also, providing sexual experience to low SC yearling bulls can improve SC and should be a standard part of the test. Scrotal circumference and breeding soundness examination scores, both traditional measures of bull fertility, were unrelated to SC.
Keywords: Cattlemen& #x27; s Day; 1987; Kansas Agricultural Experiment Station contribution; no. 87-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 514; Beef; Yearling bulls; Scrotal circumference; Breeding soundness